2013
DOI: 10.1111/jog.12231
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to ambient air pollutants and spontaneous abortion

Abstract: Our findings suggest that pregnant women exposed to ambient air pollutants may be at increased risk of spontaneous abortion. Confirmation by further research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 43 publications
3
21
0
3
Order By: Relevance
“…The authors found a correlation of 80–90%, depending on the pollutant in consideration. Moridi et al (2014) investigated the association between spontaneous abortion and ambient pollutants. The authors estimated the mean exposure to pollution for each of 296 women in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found a correlation of 80–90%, depending on the pollutant in consideration. Moridi et al (2014) investigated the association between spontaneous abortion and ambient pollutants. The authors estimated the mean exposure to pollution for each of 296 women in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…These levels of CO may interfere with tissue oxygenation levels in the fetus, possibly leading to fetal death, as has been demonstrated in animal models [34]. A recent retrospective case control study in Tehran demonstrated that CO was more toxic with respect to spontaneous abortion than other pollutants, while no significant effect was identified for SO 2 [24]. In contrast, other studies have concluded that exposure to high levels of SO 2 and total suspended particulate (TSP) but not PM 10 and NO 2 during the first month of pregnancy was associated with increased risk of fetal loss [23].…”
Section: Discussionmentioning
confidence: 99%
“…One retrospective epidemiological study provided evidence for an association between brief exposure to high levels of ambient particulate matter during the preconceptional period and early pregnancy loss and found a 2.6-fold increased risk of spontaneous miscarriage [22]. More recent investigations in China [23] and Iran [24] also reported an increased risk of fetal loss in early pregnancy during exposure to high levels of air pollutants. However, no report has yet addressed associations between ambient air pollution and pregnancy loss in Mongolia.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from respiratory problems, analyzing hospital admission and diagnoses in Iran also showed that air pollutants had a high correlation with acute strokes; and that long-term increases of PM 2.5 were related to ischemic strokes (Alimohammadi et al 2015). A study looking at around 300 women in Tehran, and evaluating the correlation between ambient air pollution and spontaneous abortions in the first-trimester, found that there is also heightened risk of spontaneous abortion associated with increased PM levels (Moridi et al 2014). A study in Isfahan, Iran showed how PM air pollution leads to hospitalization for respiratory diseases among children (Mansourian et al 2010).…”
Section: Morbiditymentioning
confidence: 99%